2020
DOI: 10.1093/brain/awaa332
|View full text |Cite
|
Sign up to set email alerts
|

BACE inhibition causes rapid, regional, and non-progressive volume reduction in Alzheimer’s disease brain

Abstract: In the phase 3 EPOCH trial (Clinicaltrials.gov; NCT01739348), treatment with the BACE inhibitor verubecestat failed to improve cognition in patients with mild-to-moderate Alzheimer’s disease, but was associated with reduced hippocampal volume after 78 weeks as assessed by MRI. The aims of the present exploratory analyses were to: (i) characterize the effect of verubecestat on brain volume by evaluating the time course of volumetric MRI changes for a variety of brain regions; and (ii) understand the mechanism t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 22 publications
1
44
0
1
Order By: Relevance
“…Declarations Data described in this report was compiled post hoc (by MB) from the clinical cohorts described in references [17][18][19][20][21][22][23][26][27][28]. Each of the studies reported was conducted with the principles of the Declaration of Helsinki, the Good Clinical Practise: Consolidated Guideline approved by the International Conference on Harmonisation and applicable national and local laws and regulations.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Declarations Data described in this report was compiled post hoc (by MB) from the clinical cohorts described in references [17][18][19][20][21][22][23][26][27][28]. Each of the studies reported was conducted with the principles of the Declaration of Helsinki, the Good Clinical Practise: Consolidated Guideline approved by the International Conference on Harmonisation and applicable national and local laws and regulations.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Each of the studies reported was conducted with the principles of the Declaration of Helsinki, the Good Clinical Practise: Consolidated Guideline approved by the International Conference on Harmonisation and applicable national and local laws and regulations. The Ethical boards for the specific studies are listed: GE: statement of ethics compliance (and committees) in Wolk et al 2018 [48]; KAROLINSKA: Ethical approval was obtained from the Regional Human Ethical Committee of Stockholm (2016-120-32); MCK: statement of ethics compliance in Sur et al 2020 [19] Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…For example, a change in the local tissue microenvironment associated with amyloid plaques or tau tangles-associated elicited by an Alzheimer's disease therapeutic candidate targeting one of those pathologies could result in effects on brain atrophy that reflect the underlying distribution of that pathology. Preferentially increased brain volume loss in regions with high amyloid load was recently reported for a phase 3 trial of the BACE inhibitor verubecestat in mild-to-moderate Alzheimer's disease [187]. The increasing availability of PET tracers for other pathological targets (tau for Alzheimer's disease, with more under development for other pathologies) will enable such effects, if present, to be revealed across different therapeutic approaches and neurological disorders.…”
Section: Relationship To Anatomical Distribution Of Targetmentioning
confidence: 87%
“…Fig 6. Schematic illustrating the interpretive value of intermediate scans, similar to data observed in[187]. (a) A transient increased volume loss relative to placebo immediately after treatment initiation, with no long-term change in the rate of atrophy, can be detected and…”
mentioning
confidence: 77%
See 1 more Smart Citation